THE ROLE OF FINANCIAL DISTRESS AND THIN CAPITALIZATION IN CORPORATE TAX AGGRESSIVENESS - Putri , Rizma Fatmawati; Akbar, Fajar Syaiful (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2025)
This research addresses the persistent issue of corporate tax aggressiveness, focusing on companies listed Indonesia’s property and real estate sector. The primary objective is to analyze how financial distress and thin capitalization influence tax aggressive practices among firms listed on the Indonesia Stock Exchange during the 2021-2023 period. Adopting a quantitative methodology with purposive sampling, the study utilizes multiple linear regression to analyze data from a sample of 96 companies. Financial distress is found to have a statistically significant and positive impact on tax aggressiveness, while thin capitalization does not exhibit a considerable influence. These findings suggest the need for more targeted tax regulations and enhanced oversight. Future research is encouraged to include additional variables and broaden the sample to cover multinational firms for a more comprehensive understanding of tax aggressiveness behavior.